2021
DOI: 10.1101/2021.02.16.21251838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profile of SARS-CoV-2-specific CD4 T cell response: Relationship with disease severity and impact of HIV-1 and activeMycobacterium tuberculosisco-infection

Abstract: T cells are involved in control of COVID-19, but limited knowledge is available on the relationship between antigen-specific T cell response and disease severity. Here, we assessed the magnitude, function and phenotype of SARS-CoV-2-specific CD4 T cells in 95 hospitalized COVID-19 patients (38 of them being HIV-1 and/or tuberculosis (TB) co-infected) and 38 non-COVID-19 patients, using flow cytometry. We showed that SARS-CoV-2-specific CD4 T cell attributes, rather than magnitude, associates with disease sever… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Describing mortality risk among these groups is important because studies have shown that among patients with SARS-CoV-2 infection, those who also had HIV and tuberculosis had altered T-cell functions and were at risk of more severe disease. 28 Large population cohorts from the Western Cape province of South Africa 18 and the UK 19,20 and more recent metaanalyses [21][22][23] found people with HIV to have an increased risk of COVID-19 mortality, with increased in-hospital mortality reported in the Western Cape 18 and UK 19 studies. Our study, however, could not conclude that HIV is a risk factor at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…Describing mortality risk among these groups is important because studies have shown that among patients with SARS-CoV-2 infection, those who also had HIV and tuberculosis had altered T-cell functions and were at risk of more severe disease. 28 Large population cohorts from the Western Cape province of South Africa 18 and the UK 19,20 and more recent metaanalyses [21][22][23] found people with HIV to have an increased risk of COVID-19 mortality, with increased in-hospital mortality reported in the Western Cape 18 and UK 19 studies. Our study, however, could not conclude that HIV is a risk factor at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that HIV is associated with an increased risk of more severe disease and death from COVID-19 17 , although in most studies the association is modest 36-39 . Two studies from South Africa have demonstrated that HIV is associated with suboptimal CD4+ T-cell and humoral immune responses to SARS-CoV-2, particularly in the absence of suppressive ART 17,40 ; and one study from the United States suggested that HIV is associated with lower neutralizing antibody titres following natural infection 41 . In the case described here, based on the very low CD4+ count there was putative immunosuppression as a result of antiretroviral treatment failure and HIV drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, T cell responses can confer protection even in the absence of humoral responses, given that, patients with inherited B cell deficiencies or hematological malignancies are able to fully recover from SARS-CoV-2 infection ( 22 ). In some instances, COVID-19 disease severity has been attributed to poor SARS-CoV-2-specific CD4 + T cell polyfunctionality potential, reduced proliferation capacity and enhanced HLA-DR expression ( 14 ). Importantly, a recent study identified nonsynonymous mutations in known MHC-1-restricted CD8 + T cell epitopes following deep sequencing of SARS-CoV-2 viral isolates from patients, demonstrating the capacity of SARS-CoV-2 to escape from CTL recognition ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Larger epidemiological studies have demonstrated increased hospitalization and higher rates of COVID-19-related deaths among PLWH compared with HIV negative individuals (10)(11)(12)(13). Other studies have linked HIV mediated CD4⁺ T cell depletion to suboptimal T cell and humoral immune responses to SARS-CoV-2 (14). A recent study showed prolonged shedding of high titre SARS-CoV-2 and emergence of multiple mutations in an individual with advanced HIV and antiretroviral treatment (ART) failure (15).…”
Section: Introductionmentioning
confidence: 99%